PENYIDIKAN TINDAK PIDANA YANG DILAKUKAN OLEH ANAK BERDASARKAN UNDANG-UNDANG NOMOR 11 TAHUN 2012 TENTANG SISTEM PERADILAN PIDANA ANAK OLEH PENYIDIK KEPOLISIAN SEKTOR KOTO TANGAH KOTA PADANG - Adha, Aditya; Diana, Ledy; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Criminal Acts are acts committed by human beings who may be liable in which the act is prohibited or ordered or permitted by law which is sanctioned in the form of criminal sanction. A child is a person who is not yet 18 (eighteen) years of age, including a child still in the womb. The number of crimes committed by children at this time could adversely affect the lives of children in the future. The investigation of a crime committed by a child is carried out by a special police investigator to conduct an investigation of the child. Associated children who deal with the law are regulated in Law Number 11 Year 2012 on the Criminal Justice System of Children. As for the purpose of writing this thesis is, First to find out the investigation of criminal acts committed by children based on Law Number 11 Year 2012 About the Criminal Justice System of Children by police investigators Sector Koto Tangah Padang City. Secondly, to find out the settlement of crime committed by the child is in accordance with Law Number 11 Year 2012 on the Criminal Justice System of Child by Police Sector investigator Koto Tangah Padang City.The method of research in this study, using the type of juridical sociological research is Criminal Acts is an act committed human beings who can be responsible where the act is prohibited or ordered or permitted by law that is given sanctions in the form of criminal sanctions with research sites in the Police Sector Koto Tangah Padang City. In this study conducted data collection by way of interviews, and literature review. After the data collected then analyzed qualitatively, then drawn the conclusion with deductive method that is analyze the problem from the general shape to the special form.From the result of the research, it can be concluded that the first investigation of criminal acts committed by the child by the investigator of Police Sector Koto Tangah Padang City during the investigation process did not distinguish between the criminal investigation conducted by the adult and the criminal investigation conducted by the child and in the case of the placement of the detention children are not placed in special room for children services as referred to in Law Number 11 Year 2012 on Child Criminal Justice System. second, the settlement of criminal acts committed by children there is incompatibility with Law Number 11 Year 2012 on the Criminal Justice System of Children namely that not all crimes committed by children can be resolved in the field of investigation through the diversi, and in the settlement of crimes committed by children through the Koto Tangah Police Sector's investigative division of Padang City excludes the Community Guard and Correctional Center.Keywords: Investigation - Crime - Child